PENGARUH PENINGKATAN KONSENTRASI PEKTIN SEBAGAI GELLING AGENT TERHADAP SIFAT FISIK MARSHMALLOW ANTISARIAWAN EKSTRAK KENTAL DAUN SAGA (Abrus precatorius L.) - rahmah elfiyani; ari widayanti; budiarti rahayu (Farmasains : Jurnal Ilmiah Ilmu Kefarmasian, 2016)
Saga leaves (Abrus precatorius L.) have anti-thrush activity and contain glisirizin. Glisirizin is a compound of saponin glycosides non hemolytic, class of triterpenoid and have anti-parasitic activity. This study aims at knowing effect of increasing concentration of pectin as gelling agent on physical properties marshmallow. Saga leaves extract made in to marshmallow 4 formulas, with variations of concentrations of pectin 0.7%, 0.8%, 0.9% and 1%. The physical properties evaluations included organoleptic, uniformity of weight, uniformity of size, moisture content, and texture. The hardness test result data obtained in 859.33; 710.03; 677.13; 506.36 gf, the cohesiveness test result data 0.7375; 0.8247; 0.8780; 0.9327 gs, the springiness test result data 0.7255; 0.8142; 0.8530; 1.0236 gs. Data were analysed using one-way ANOVA followed by Tukey test. The result showed that the higher concentration of pectin will increase springiness and cohesiveness and reduce hardness of marshmallow of viscous saga leaves extract.